A Coumarin-Based Fluorescence Probe for Selective Recognition of Cu2+ Ions and Live Cell Imaging. (30th October 2019) - He, Guangjie; Ma, Nana; Li, Linlin; Xie, Chenyan; Yang, Linlin; Xu, Jinhe; Wang, Junli
Abstract : A new fluorescence probe L was rationally designed and synthesized for the recognition of Cu 2+ ions by the combination of coumarin hydrazide and 2-acetylpyrazine. The photochemical properties and selectivity of L for Cu 2+ ions in a CH3 CN/HEPES (3 : 2, v / v ) buffer were investigated by UV-vis absorption and fluorescence emission spectra. A highly selective and sensitive response of L for Cu 2+ ions over other competing metal ions was observed with limit of detection in 3  μ M. The coordination stoichiometry of L to Cu 2+ ions was determined to be 1 : 1 by the UV-vis absorption spectrum, the fluorescence titrations, and density functional theory (DFT) calculations. Moreover, L was applied successfully for recognition of intracellular Cu 2+ ions in living cells.